Best practice criteria of inclusive playground equipment for Children With Disabilities (CWD) / Raja Mohd Aizat Akhmal Raja Mohd Rozuan, Kharizam Ismail and Wan Rabiah Wan Omar - Raja Mohd Rozuan, Raja Mohd Aizat Akhmal; Ismail, Kharizam; Wan Omar, Wan Rabiah (2022)
One of the important elements in children’s development is playing where they interact, develop communication skills, build self-confidence, maintain and improve health conditions, and so forth. All children including children with disabilities have equal rights to enjoy playing with friends during their childhood development. In supporting this need, the government has made it compulsory for local authorities to ensure their area of jurisdiction is provided with public playgrounds. Unfortunately, it was found that most of these public playgrounds did not support the special needs of children with disabilities (CWD). Hence, the precious childhood play experience for children with disabilities was found to be very limited. In Malaysia, there is a dearth of research on the needs of public facilities of playgrounds especially for play equipment suited for children with physical disabilities. The Social Welfare Department in 2020 stated that Selangor has recorded 16% of their children are physically disabled and this figure is the highest among all the states in Malaysia. Due to this situation, this particular study is focussing on developing best practice criteria in the design of inclusive playground equipment that can be enjoyed by all children including CWD. This research applied the quantitative approach whereby data were obtained using a questionnaire survey distributed to parents and caretakers of children with disabilities in Selangor. The collected data was analyzed using Mean Rank Analysis. Results show that there are five main criteria namely usable equipment, sufficient space, reachable height, safe play material, and helpful features of play equipment as best practice elements in providing friendly, accessible and safe playground equipment for children with disabilities. It is hoped that this research can assist the local authority and the playground provider to provide inclusive playground equipment that is suitable for all children especially children with disabilities. This will encourage all children to mix and socialize during playtime without any prejudice.